2021
DOI: 10.3390/su13041914
|View full text |Cite
|
Sign up to set email alerts
|

Components of Countries’ Regulative Dimensions and Voluntary Carbon Disclosures

Abstract: The previous literature has demonstrated that countries’ regulative contexts positively influence voluntary corporate carbon disclosures. However, little research has been conducted into the relationship between the different components of the regulative dimension of institutions and voluntary carbon disclosure. Drawing on the theoretical framework of New Institutional Sociology (NIS), this study examines the influence of the different components of the regulative context (rules; monitoring mechanisms and puni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 70 publications
(193 reference statements)
0
2
0
Order By: Relevance
“…In spite of the rising number of studies on climate change and carbon disclosures [16][17][18][19], there is still a lack of research on the role of government reform and regulatory change in the disclosure of carbon emissions. Moreover, reference [20] called for further studies to look at climate change accounting and accountability by examining climate change-related disclosures.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the rising number of studies on climate change and carbon disclosures [16][17][18][19], there is still a lack of research on the role of government reform and regulatory change in the disclosure of carbon emissions. Moreover, reference [20] called for further studies to look at climate change accounting and accountability by examining climate change-related disclosures.…”
Section: Introductionmentioning
confidence: 99%
“…Regulations and rules shape the landscape of the financial market. For example, Mateo-Marquez et al (2021) demonstrated that regulative pressure is a significant factor that influence the probability of a firm's voluntary carbon disclosure, and in particular, climate-related rules and rewards have a positive correlation with the quality of the disclosure. However, there has been no academic literature that specifically focuses on the reform of the green insurance market from the regulative perspective.…”
Section: Regulative Pillarmentioning
confidence: 99%